The self in neuroscience and psychiatry - Kircher, Tilo, 1965-; David, Anthony S. (Cambridge University Press, 2003)
In recent years neuroscience has contributed important insights to the concept and construction of the self from conditions, such as schizophrenia, in which the self becomes disordered. This book focuses on neuropsychiatric models of self-consciousness, set against introductory essays describing the philosophical, historical and psychological approaches.